2019
DOI: 10.1021/acs.jafc.9b01564
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Key Aroma Compounds in Beijing Roasted Duck by Gas Chromatography–Olfactometry–Mass Spectrometry, Odor-Activity Values, and Aroma-Recombination Experiments

Abstract: The dominant aroma compounds in the breast skin and breast muscle of Beijing roasted duck were investigated by gas chromatography−olfactometry−mass spectrometry (GC-O-MS), odor-activity values, and aroma recombination. The results demonstrated that a total of 42 aroma compounds were identified in Beijing roasted duck, including aldehydes, ketones, alcohols, acids, phenols, sulfur-containing compounds, and nitrogen-containing compounds. Among the 42 aroma compounds, 18 were identified as important odorants with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(111 citation statements)
references
References 43 publications
1
110
0
Order By: Relevance
“…Among them, the content of 1‑octen‐3‐ol, also known as C8‐complex low threshold volatiles, increased by 38.4 times compared with raw egg liquid. The production of 1‐octen‐3‐ol was usually attributed to degradation of linoleic acid or arachidonic acid (Edirisinghe, Graham, & Taylor, 2007; Wurzenberger & Grosch, 1982), and it is also often found in some heat‐treated foods, such as cooked red mullet, roasted duck (Liu et al., 2019; Salum, Guclu, & Selli, 2017). The above report at least proved that linoleic and arachidonic acid, which were abundant in egg lipids, might be regarded as precursors to 1‑octen‐3‐ol.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the content of 1‑octen‐3‐ol, also known as C8‐complex low threshold volatiles, increased by 38.4 times compared with raw egg liquid. The production of 1‐octen‐3‐ol was usually attributed to degradation of linoleic acid or arachidonic acid (Edirisinghe, Graham, & Taylor, 2007; Wurzenberger & Grosch, 1982), and it is also often found in some heat‐treated foods, such as cooked red mullet, roasted duck (Liu et al., 2019; Salum, Guclu, & Selli, 2017). The above report at least proved that linoleic and arachidonic acid, which were abundant in egg lipids, might be regarded as precursors to 1‑octen‐3‐ol.…”
Section: Resultsmentioning
confidence: 99%
“…In this current study, a total of 56 volatile compounds were found in samples of the duck breast muscle. Most of these volatile components in the duck breast muscle has been identi ed in beijing roasted duck [37,38]. As shown in Table 4, changes of 56 volatile compounds in duck breast muscle indicated that the lipid oxidation was inhibited effectively by dietary curcumin given to ducks.…”
Section: Discussionmentioning
confidence: 99%
“…Volatile compounds in the roasted lamb were extracted by the solid-phase microextraction (SPME) method and subsequently analysed by gas chromatography coupled to mass spectrometry (GCMS-QP 2010 Plus, Shimadzu, Kyoto, Japan) according to the literature reported by Liu et al [23]. The extraction conditions were as follows: 2.0 g of minced sample were placed in a 20 mL headspace vial, and 1.5 µL of internal standard (2-methyl-3heptanone, 1.68 µg/µL in methanol) was added, the vial sealed with a PTEE-silicon stopper.…”
Section: Determination Of Volatile Compoundsmentioning
confidence: 99%
“…The concentrations of the volatile compounds were calculated according to the ratio between peak area and the concentration of 2-methyl-3-heptanone. The contribution of volatile compounds to the flavour of roasted lamb were evaluated by odour activity values (OAVs), which were calculated as the ratio of the compound concentration to the perception threshold described in the literature [23] and the book of compilations of odour threshold in air, water, and other media [25]. The major contributors of the roasted meat flavour were generally considered to be volatile compounds with OAVs > 1 [26].…”
Section: Determination Of Volatile Compoundsmentioning
confidence: 99%